2006
DOI: 10.1063/1.2397543
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of the effect of water adsorption on the carbon nanotube field-effect transistor

Abstract: Articles you may be interested inAb-initio calculations for a realistic sensor: A study of CO sensors based on nitrogen-rich carbon nanotubes AIP Advances 2, 032115 (2012); 10.1063/1.4739280Conductance of individual channels in a carbon nanotube field-effect transistor studied by magnetic force microscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 29 publications
2
60
0
Order By: Relevance
“…21,[25][26][27][28] This weak interaction has been shown to cause little scattering, and the conductance of individual CNTs when hydrated is little changed from when dry. 26,29 Charge transfer analyses, also performed within DFT, have suggested that water may n-dope CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…21,[25][26][27][28] This weak interaction has been shown to cause little scattering, and the conductance of individual CNTs when hydrated is little changed from when dry. 26,29 Charge transfer analyses, also performed within DFT, have suggested that water may n-dope CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…[117][118][119][120] Internal wetting produces exactly the opposite result: the threshold moves to more positive gate bias and the hysteresis decreases.…”
Section: Cnt Device Design and Experiments Methodsmentioning
confidence: 99%
“…V ds = 0.8V for both (a) and (b). (c) I ds time traces during adding water into the reservoirs for both unopened and opened tubes at V ds = 0.8 V and V gs = 10 V. 124 Studies of external wetting [117][118][119][120] have been carried out using a window opened in dielectric material that covers the metallic contacts (Figure 6.5).…”
Section: Cnt Device Design and Experiments Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Li et al, 2003;Karthigeyan, et al, 2008;Maeng, et al, 2008-a) The use of microheaters is highly recommendable as the characteristics of SWCNT devices are affected by humidity. (Sung et al, 2006) Carbon nanotubes are also known to exhibit higher sensitivity at moderately elevated temperature range. (Valentini, et al,2003) It is, thus, desirable for SWCNTs network to become monolayer so that the temperature of microheater and the nanotubes coincides during the operation.…”
Section: Future Prospects Of Swcnt Network Gas Sensormentioning
confidence: 99%